The Effect of Differentiated Learning Strategies on Student’s Learning Outcomes - Sulistyaningsih, Dewi Ayu (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
The purpose of this study is to determine the influence of differentiated learning strategies on student’s learning outcomes. The research was conducted using an experimental method with a pretest-posttest control group design. Data were collected through a learning outcome test and analyzed using a t-test. The results showed that there was a significant difference in learning outcomes between the group that used differentiated learning strategies and the control group that did not use learning strategies. The group that used differentiated learning strategies had a score of 87.12. Meanwhile, the group that did not use learning strategies was 66.96. This means that there is an influence of differentiated learning strategies on student learning outcomes. The results of this study have the implication that differentiated learning strategies can be an alternative for teachers to improve student learning outcomes.